2015
DOI: 10.19154/njwls.v5i2.4792
|View full text |Cite
|
Sign up to set email alerts
|

Job Insecurity and Mental Well-Being in Finland, Norway, and Sweden

Abstract: This article describes how the flexicurity arrangement of low job security KEY WORDSFlexicurity / job insecurity / mental well-being / employment security / income security / cognitive and affective insecurity

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Several processes related to the labor market influence the worker's opportunities -representing increase or decrease of control -for positioning himself or herself according to own preferences. Examples of such constantly ongoing processes influencing opportunities for control are stratification into core and peripheral workers, threats of unemployment, change in employment levels, new organizational paradigms, and organizational downsizing as a tool for restructuring the workplace (Ferrie et al 2008;Vahtera & Virtanen 2013;Vulkan et al 2015).…”
mentioning
confidence: 99%
“…Several processes related to the labor market influence the worker's opportunities -representing increase or decrease of control -for positioning himself or herself according to own preferences. Examples of such constantly ongoing processes influencing opportunities for control are stratification into core and peripheral workers, threats of unemployment, change in employment levels, new organizational paradigms, and organizational downsizing as a tool for restructuring the workplace (Ferrie et al 2008;Vahtera & Virtanen 2013;Vulkan et al 2015).…”
mentioning
confidence: 99%
“…153-154, 171;Bergold & Vedin, 2015, p. 10;Håkansson, 2001, p. 71). Comparative research in Finland, Norway, and Sweden shows that job, employment, and income insecurity all are related to mental health (Vulkan et al, 2015). The findings in this study reveal the ways in which such working conditions aggravate the conflict between working life and family life, and show that a crucial dimension of this is that they make it difficult to act in accordance with ethical ideals about good mothering.…”
Section: Concluding Discussionmentioning
confidence: 67%
“…In another study conducted by Cheng and her colleague in Great Britain, it was shown that occupational prestige was significantly associated with high mental wellbeing ( 39 ). Various studies around the world have examined the significance of employment, job quality, job security, working capacity, workplace stress and working environment on PMH ( 31 , 40 43 ). Another important PMH need prioritized at the differential exposure level is providing proper working conditions.…”
Section: Discussionmentioning
confidence: 99%